ULGURJI SAVDO KORXONALARINING ULGURJI SAVDO AYLANMASI VA UNI OSHIRISHDAGI MUAMMOLAR (Marketing Journal, 2026)
AbstractThis article comprehensively examines the mechanisms of wholesale tradeturnover formation and the problems hindering its growth. The role of wholesale trade in the economy, its function in balancing supply and demand, and its intermediary rolebetween producers and consumers are theoretically substantiated.The study analyzes the key performance indicators of wholesale enterprises, theefficiency of working capital utilization, the turnover ratio and turnover period ofworking capital, the level of inventory turnover, and the average daily trade volume.Based on the results of the analysis, scientifically grounded proposals andrecommendations aimed at increasing wholesale trade turnover have been developed.Keywords: wholesale trade turnover, inventory, logistics costs, transportationcosts, warehousing costs, packaging and loading expenses, ratio of trade turnover toaverage working capital, average daily wholesale turnover, service processes atstrategic and operational levels.